Influence of Fomo and Flash Sale on Doom Spending with Impulsivity Moderation in Balinese Students - I Kadek Yoga Rama Parmita; Liem Bambang Sugiyanto; Lexi Pranata Budidharmanto; Fahrul Riza (Journal of Economics and Management, 2026)
This study examines the effects of Fear of Missing Out (FOMO) and flash sales on doom spending behaviour among Generation Z college students in Bali Province, with impulsivity as a moderating variable. A quantitative approach was employed using online and offline questionnaires distributed to 200 respondents selected through purposive sampling from several universities in Bali. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The findings show that both FOMO and flash sales have a positive and significant effect on doom spending behavior. However, impulsivity does not significantly moderate the relationship between FOMO and doom spending, nor between flash sales and doom spending. These results indicate that doom spending among Generation Z is directly influenced by digital promotional stimuli and emotional pressure, regardless of individual impulsivity levels. The study highlights the dominant role of digital promotional stimuli in shaping consumer behavior. Practically, the findings suggest that consumers need greater awareness and self-control when responding to time-limited promotions and socially driven purchasing pressure. For sellers and platform managers, the results provide insights for designing effective promotional strategies while encouraging responsible consumption. This study is limited to Generation Z college students in Bali and relies on self-reported data. Future research is recommended to expand the sample and include additional variables, such as financial literacy, self-control, and emotional regulation.